Modern Philosophy - "Schwegler, Albert" (Calcutta, 1982)
Schwegler's Handbook of the History Philosophy, surveying the philosophical activity in Europe from Thales to Hegel, ahs all the excellence of a masterpiece and a classic. No less a philosopher than J.H. Stirling considered it "a work of gratitude'; to translate it from German into English. While doing it, Stirling observed, "How this excellence has originated will be understood at once, when we consider that Schwegler, a remarkable ripe full man, and possessed of the gift of style, wrote this History, so to speak, at a single stroke of the pen...
Keywords: Philosophy